Bullous Systemic Lupus Erythematosus Mimicking Bullous Pemphigoid: A Case Report - Vesri Yossy; Gardenia Akhyar; Alimuddin Tofrizal (Universitas Baiturrahmah, 2021)
Introduction: Bullous systemic lupus erythematosus (BSLE) is an infrequent but distinct presentation of systemic lupus erythematosus (SLE) in less than 5% of lupus cases. It is characterized by vesicobullous skin eruption in SLE that can develop either before or after SLE diagnosis has been established. Distinguish between BSLE with other autoimmune blistering diseases such as bullous pemphigoid (BP), dermatitis herpetiformis, linear IgA, etc., is very important to prevent misdiagnosis. The physician must be able to combine clinical, histological and immunofluorescence finding for the diagnosis approach. We report a case of blistering skin eruption in SLE patient. Case Report: A 19-year-old female patient complained of tense blistering on her lip, face and wrists since one month ago. She was diagnosed with SLE two weeks ago. The dermatological state showed bullae and vesicle on erythematous/ normal base, erosions, excoriation and blackish red crust on the lip, face, armpit, neck, abdomen and wrists. Histopathological examination of the lesion showed sub-epidermal bullae containing PMN leukocytes consist of abundant neutrophils, only occasional eosinophils and the presence of keratotic plugs. Direct immunofluorescence (DIF) of the skin showed linear deposition of IgG, IgA, IgM and C1q at the dermo-epidermal junction. This patient exhibited similar features to both BSLE and BP with tensed clear blisters and subepidermal cleft. BSLE differ from BP by abundant neutrophils found on histopathological examination, whereas BP has abundant eosinophils. Conclusion: Immunofluorescence examination shows linear IgG in BP, whereas linear or granular IgG in BSLE. Establishing the correct diagnosis is important to prevent misdiagnosis and mistreatment.